2024
DOI: 10.1007/s12325-023-02732-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Upadacitinib in Immune-Mediated Inflammatory Diseases: Systematic Literature Review of Indirect and Direct Treatment Comparisons of Randomized Controlled Trials

Eduardo Mysler,
Gerd R. Burmester,
Christopher D. Saffore
et al.

Abstract: Introduction Immune-mediated inflammatory diseases including rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS), non-radiographic axial spondylarthritis (nr-axSpA), atopic dermatitis (AD), ulcerative colitis (UC), and Crohn’s disease (CD) pose a substantial burden on patients and their quality of life. Upadacitinib is an orally administered, selective, and reversible Janus kinase inhibitor indicated for seven conditions, but data on its safety versus other active tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In the three studies with abrocitinib, including 787 patients with AD, no cases of cancer were reported [ 77 , 99 , 100 ]. Regarding upadacitinib, a recent SR including 25 RCTs (> 10,000 patients) reported that most of the RCTs did not find a significant increase in the rate of malignancies with upadacitinib therapy when compared to placebo or to anti-TNFs [ 101 , 103 , 105 ]. However, an extended study of a phase 3 RCT (493 patients with RA) showed a higher rate of neoplasia in the 12 mg/day group, mainly at the expense of NMSC [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the three studies with abrocitinib, including 787 patients with AD, no cases of cancer were reported [ 77 , 99 , 100 ]. Regarding upadacitinib, a recent SR including 25 RCTs (> 10,000 patients) reported that most of the RCTs did not find a significant increase in the rate of malignancies with upadacitinib therapy when compared to placebo or to anti-TNFs [ 101 , 103 , 105 ]. However, an extended study of a phase 3 RCT (493 patients with RA) showed a higher rate of neoplasia in the 12 mg/day group, mainly at the expense of NMSC [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found nine studies on the risk of neoplasms with selective JAK 1 (JAK-1) inhibitors: three focusing on abrocitinib [77,99,100] and six on upadacitinib [55,[101][102][103][104][105]. In the three studies with abrocitinib, including 787 patients with AD, no cases of cancer were reported [77,99,100].…”
Section: Jak-1 Inhibitors (Abrocitinib Upadacitinib) and Cancer Riskmentioning
confidence: 99%